ANALISIS PENERAPAN SANKSI PIDANA TERHADAP OPTIK YANG BEROPERASI TANPA IZIN PRAKTIK OPTOMETRIS DI KOTA SERANG - Tituk Yuana Widiyati; Ismail; Rendi Kahfi Septiana; Dadi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the application of criminal sanctions against opticians operating without an optometrist practice permit in Serang City. A refraction examination conducted by an optician without a licensed optometrist is a violation of statutory provisions, specifically Law Number 17 of 2023 concerning Health. If these obligations are not met, it will have a serious impact on patient safety, can reduce the quality of eye health services, and create public distrust of optometrists. The research method used is normative juridical by analyzing various laws and regulations as the main legal sources, including Law Number 17 of 2023, Law Number 36 of 2014 and other related regulations. In addition, the research is also supported by empirical data through interviews with various parties. This study shows that of the 30 actively operating opticians, only 16 optometrists have a practice permit in Serang City. Although criminal sanctions have been regulated normatively, ranging from administrative sanctions to imprisonment and fines are also possible. However, its implementation has not been optimal due to limited supervision, low legal awareness of optical business actors, weak coordination between the Health Service, law enforcement officers, and professional organizations and lack of education to the public about the importance of refractive services by Optometrists. This study concludes that normatively law enforcement is adequate, but its effectiveness depends on stricter supervision by various related parties, structured law enforcement mechanisms, ongoing legal education to Optical business actors to improve compliance and public health protection and educate the public about the importance of eye examinations by officially licensed Optometrists.